Pemanfaatan Teknologi Informasi Dalam Pengambilan Keputusan Penilaian Karyawan Terbaik - Dinda Amalia; Trio; Kiky Mayra Asyiva Nst; Yohanes Naibaho; Dodoan Ariando Butar-Butar (CV. Utility Project Solution, 2020)
The development of Information Technology has enabled decision making to be done more quickly and accurately. The use of computers has evolved from simply processing data and presenting information, to being able to provide choices to support decision makers. Human Resources (HR) is a very important factor that cannot be separated from an organization, both institutions and companies. HR is also the key that determines the company's development. Decision support systems can assist in the decision-making process to determine the best choice based on criteria, so that the best employees can be selected more quickly and more objectively. From the above problems the authors are interested in creating a system which is expected to be able to help make a decision that is implemented in the form of computerized software. The basic concept of the SimpleAdditiveWeighting method is to find the weighted sum of the performance ratings for each alternative on all criteria. From the calculations that have been done, the ranking results can be selected to select the best employee, from the image below it is clear that A. Dahlan gets the highest score, it can be said that the best employee.